KEPEMIMPINAN KEPALA SEKOLAH BERDASARKAN KECERDASAN EMOSIONAL (EQ) DI DI SMP NEGERI 2 TANJUNG LUBUK KABUPATEN OGAN KOMERING ILIR - Nety Heryani Komalasari (UNISAN JURNAL, 2024)
This research is a qualitative study that describes the leadership of the Principal of SMP 2 Tanjung Lubuk and analyzes the emotional intelligence perspective. This research was carried out using observation, interviews and documentation techniques. Testing the validity of the data uses triangulation techniques, where in this research more emphasis is placed on source triangulation techniques. The source is all teachers and staff at SMP 2 Tanjung Lubuk. This source will contain data on the leadership of the Principal of SMP 2 Tanjung Lubuk based on emotional intelligence. The results of the analysis show that the principal carries out primal leadership very well. This is proven by triangulation of data and sources. The Principal of SMP 2 Tanjung Lubuk has a high commitment to the vision of the future, especially in times of stress or in the midst of increasing responsibilities. The chairman of the foundation took an emotional approach to all residents in the foundation. The Foundation Chair is able to read his own emotions and recognize their impact using instinct to guide decisions, knows his strengths and limitations, is able to control his emotions and shows honesty and integrity, can be trusted. The principal has good self-awareness and self-management, good social awareness and good relationship management Keywords : Leadership, Principal, Emotional Intelligence